2008
DOI: 10.1016/j.jcrs.2007.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of refractive surgery candidates with Placido topography, Orbscan II, Pentacam, and wavefront analysis

Abstract: Several parameters provided by the Pentacam, Orbscan II, WaveScan, and pachymetry were statistically correlated with keratoconus suspect, defined by higher asymmetry and steeper curvature on Placido topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 19 publications
(23 reference statements)
3
80
0
2
Order By: Relevance
“…[14][15][16][20][21][22] Specifically, in keratoconus and also in keratoconus suspect, significantly larger values of BFS 14,16,21 and posterior elevation 15,16,22 have been reported (Figure 3). Schlegel et al 16 report a mean aconic astigmatism for the posterior corneal surface of 2.29 D G 1.71 (SD) in a sample of 48 keratoconussuspect patients using scanning-slit technology.…”
Section: Analysis Of the Posterior Corneal Surface In Keratoconusmentioning
confidence: 87%
See 2 more Smart Citations
“…[14][15][16][20][21][22] Specifically, in keratoconus and also in keratoconus suspect, significantly larger values of BFS 14,16,21 and posterior elevation 15,16,22 have been reported (Figure 3). Schlegel et al 16 report a mean aconic astigmatism for the posterior corneal surface of 2.29 D G 1.71 (SD) in a sample of 48 keratoconussuspect patients using scanning-slit technology.…”
Section: Analysis Of the Posterior Corneal Surface In Keratoconusmentioning
confidence: 87%
“…The term keratoconus suspect was coined for designating corneas not showing biomicroscopic keratoconic signs but subtle topographic features similar to early stages of keratoconus. [14][15][16][17][18][19] In such conditions, other diagnostic tests and examinations may be helpful to confirm the potential presence of an incipient ectatic condition.…”
Section: J Cataract Refract Surg 2012; 38:2167-2183 Q 2012 Ascrs and mentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 The disease has been shown to be more prevalent also in patients searching for refractive surgery, as a consequence of self-selection bias, due to their refractive error. [33][34][35][36][37] A study in Colombia reported 3.9% prevalence in a group of patients that underwent an ophthalmic evaluation in a refractive surgery center. 37 In Yemen, prevalences of 15.5% of keratoconus and 9.4% of forme fruste keratoconus were found among refractive surgery candidates.…”
Section: Epidemiologymentioning
confidence: 99%
“…33 In a study in the United States, 25.5% of eyes evaluated for refractive surgery met the Rabinowitz criteria for keratoconus suspect. 34 A vast majority of the studies state that the age of onset of the disease is between 20 and 30 years. Some studies report a higher prevalence in male patients, whereas others indicate that there is no significant difference between genders.…”
Section: Epidemiologymentioning
confidence: 99%